2012
DOI: 10.1089/thy.2011.0183
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Vasoreactivity in Subjects with Thyroid Autoimmunity and Subclinical Hypothyroidism Before and After Supplementation with Thyroxine

Abstract: In asymptomatic subjects with SCH due to thyroid autoimmunity, coronary microvascular function is impaired and improves after supplementation with LT4. This may partially explain the increased cardiovascular risk attributed to SCH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
0
10
0
5
Order By: Relevance
“…However, several PET scan studies of DCM patients suggest they may also have impaired coronary blood flow due to microvascular alterations (211,248). Several studies have also shown impaired coronary blood flow in noncardiac patients with scHypo (15,244), largely reversible with TH treatment. The high incidence of low TH function in DCM patients, coupled with the likely presence of impaired coronary blood flow from this condition, suggests that many from this patient group may benefit from TH treatment.…”
Section: Low Thyroid Function and Heart Diseasementioning
confidence: 99%
“…However, several PET scan studies of DCM patients suggest they may also have impaired coronary blood flow due to microvascular alterations (211,248). Several studies have also shown impaired coronary blood flow in noncardiac patients with scHypo (15,244), largely reversible with TH treatment. The high incidence of low TH function in DCM patients, coupled with the likely presence of impaired coronary blood flow from this condition, suggests that many from this patient group may benefit from TH treatment.…”
Section: Low Thyroid Function and Heart Diseasementioning
confidence: 99%
“…There is an association between subclinical hypothyroidism (SCH) and increased risk for cardiovascular disease as shown in a study performed by Traub-Weidinger et al examining coronary vascular reactivity in asymptomatic patients with SCH before and after levothyroxine (LT4) supplementation [41]. In asymptomatic subjects with SCH due to thyroid autoimmunity, coronary microvascular function was impaired and improved after supplementation with LT4.…”
Section: Hormonal Influences On Vascular Reactivity: At the Heart mentioning
confidence: 99%
“…In asymptomatic subjects with SCH due to thyroid autoimmunity, coronary microvascular function was impaired and improved after supplementation with LT4. These findings may explain the increased cardiovascular risk attributed to SCH [41]. …”
Section: Hormonal Influences On Vascular Reactivity: At the Heart mentioning
confidence: 99%
“…As a consequence of these alterations, hypothyroid patients develop reduced renal perfusion, impaired coronary blood flow, increased arterial stiffness, and accelerated development of atherosclerosis [5][6][7][8]. Subclinical hypothyroidism has also been linked to impaired coronary blood flow in non-cardiac patients and is reversible with treatment [9,10]. A recent human study demonstrated that hypothyroid patients also exhibit high levels of vascular injury markers, closely associated with increased intima-media thickness in the common carotid artery [11,12].…”
mentioning
confidence: 99%